2017
DOI: 10.1089/jmf.2016.3844
|View full text |Cite
|
Sign up to set email alerts
|

Administration ofWasabia koreanaAmeliorates Irritable Bowel Syndrome-Like Symptoms in a Zymosan-Induced Mouse Model

Abstract: Irritable bowel syndrome (IBS) is a functional gastrointestinal disease with complex pathophysiology involving the brain-gut axis. To assess the effects of Wasabia koreana (WK) on IBS, we employed a mouse model of colonic zymosan injection presenting with diarrhea-predominant IBS-like symptoms. Oral WK administration significantly diminished stool score, suppressed colon length and weight change, and minimized body weight loss without affecting food intake. In WK-treated mice, the submucosal thickening and epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
1
22
0
1
Order By: Relevance
“…The presence of several phenolic compounds, AITC, and SA make this plant quite promising for the treatment of various diseases [ 17 , 18 ] Our group previously standardized the presence of SA and AITC in a wasabi extract. This showed that the presence of significant amounts of SA and AITC in the wasabi extract might have played an important role in the amelioration of irritable bowel syndrome-like symptoms in a zymosan-induced mouse model [ 28 ]. We also tried to understand the anti-inflammatory effect of the same extract and its representative compounds, SA and AITC, in an LPS-activated, microglia-mediated neuroinflammation model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of several phenolic compounds, AITC, and SA make this plant quite promising for the treatment of various diseases [ 17 , 18 ] Our group previously standardized the presence of SA and AITC in a wasabi extract. This showed that the presence of significant amounts of SA and AITC in the wasabi extract might have played an important role in the amelioration of irritable bowel syndrome-like symptoms in a zymosan-induced mouse model [ 28 ]. We also tried to understand the anti-inflammatory effect of the same extract and its representative compounds, SA and AITC, in an LPS-activated, microglia-mediated neuroinflammation model.…”
Section: Discussionmentioning
confidence: 99%
“…It was dried properly and grinded into a fine powder. Extraction of wasabi was performed according to the protocol described by Park et al [ 28 ], with slight modification. About 100 g of wasabi powder was extracted with 50% ethanol under sonication for about 1 h. The extract was filtered and evaporated using a rotary evaporator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zymosan-A can activate mitogen-activated protein kinases and nuclear factor-kappa B (NF-κB)[19]. However, it was used to induce an inflammation model for multiple organ dysfunction syndrome in many studies [20-23]. In the present study, we demonstrated that Zymosan-A can also provide protection against radiation-induced hematopoietic system damage by targeting the TLR2 signaling pathway after total body irradiation.…”
Section: Introductionmentioning
confidence: 54%
“…IBD is chronic and inflammatory disorder primarily involving the mucosa and submucosa of the gastrointestinal tract and patients with IBD represent a major risk factor for the development of colorectal cancer [35][36][37]. Inflammatory response has been considered as a major characteristic of IBD and it is highly associated with the occurrence of IBD [38].…”
Section: Stat3 Inhibition Blocked the Anti-inflammatory Effect Of Mirmentioning
confidence: 99%